2019
DOI: 10.1111/tbed.13377
|View full text |Cite
|
Sign up to set email alerts
|

Brucella microti‐ like prevalence in French farms producing frogs

Abstract: In the last 10 years, many atypical novel members of Brucella species have been reported, including several Brucella inopinata‐like strains in wild‐caught and “exotic” amphibians from various continents. In 2017, a strain of Brucella was isolated for the first time in animals from a French farm producing frogs—Pelophylax ridibundus—for human consumption and identified as B. microti‐like. Following this first isolation, investigations were performed in this farm as well as in the farm of the research unit that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…These results showed that B. microti ‐like organisms are able to colonise amphibians and persist in their environment. Its presence could constitute a possible risk for consumers and workers proving the importance of assessing (Jaÿ et al., ).…”
Section: Brucellamentioning
confidence: 99%
“…These results showed that B. microti ‐like organisms are able to colonise amphibians and persist in their environment. Its presence could constitute a possible risk for consumers and workers proving the importance of assessing (Jaÿ et al., ).…”
Section: Brucellamentioning
confidence: 99%
“…Other species genetically related to an atypical group within the genus have been described in different host species: Brucella microti-like in marsh frogs (Pelophylax ridibundus) [11]; Brucella vulpis in the red fox (V. vulpes) [13]; Brucella inopinata in White's and Denny's tree frogs, (Ranoidea caerulea and Zhangixalus dennysi) [169] and humans; Brucella papionis in baboons (Papio spp.) [15], without mentioning Brucella strains isolates from lungworms in porpoise (Phocoena phocoena) [170], blue-spotted ribbontail ray (Taeniura lymma) [171] and reptile panther chameleon (Furcifer pardalis) [172].…”
Section: Reservoirs In Wildlifementioning
confidence: 99%
“…In 2017, a B. microti-like strain was identified in internal organs (heart, lung, spleen, kidney, liver, and reproductive organs) and sometimes in hind limb muscles of marsh frogs in a French farm producing frogs for human consumption [11]. The human pathogenicity of amphibian strains has not been formally demonstrated but cannot be ruled out because the pathogenicity of B. microti in wild rodents has been confirmed experimentally in a mouse infection model, with high replication rates in murine macrophages [173].…”
Section: Reservoirs In Wildlifementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, B. abortus was recovered from a dog and a cat after ingestion of infected placenta materials and ingestion of milk from Brucella-positive cows [13]. A B. microti-like organism was isolated from a domestic marsh frog (Pelophylax ridibundus) and the surrounding environment in a commercial farm in France [14,15]. A novel Brucella strain similar to a B. inopinata-like sp.…”
Section: Introductionmentioning
confidence: 99%